Solar Energy-Based Fisheries Appropriate Technology Program Pokmas Water Resources Management Purwosari Village, Wonogiri - Iwan Ristanto; Annisa Azhar Firdausi Firdausi; Tantin Pristyawati; Rian Prasetyo (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Agriculture, livestock, and fisheries are key sectors that support the economic life of the majority of the Purwosari village community. They face environmental and social vulnerabilities, while also facing economic vulnerability. This is achieved by transforming traditional technologies currently used by the community to increase fisheries yields and downstream marketing through Free Nutritional Meal Kitchens (MBG) in the surrounding Wonogiri area. Strengthening village human resource development through the empowerment of Appropriate Technology (PTTG) in Purwosari Village, Wonogiri, aims to encourage energy independence in the economic activities of community groups. This includes strengthening the human resources of the Purwosari village community health post (Posyantek) for the construction of 200W solar cell TTGs and 2000W converters, solar-powered pond water pumps, and the construction of aquaculture ponds; and for freshwater fisheries. In general, the assembly of solar-powered water pump models can be adapted to field conditions and market availability. The core of this assembly is converting the electricity supply from the state electricity company (PLN) into electricity from natural sources (sunlight). The necessary equipment includes: Solar panels/solar cells (photovoltaic), controller, inverter, battery, cables, and mounting frame. The life cycle cost calculation for a solar-powered fisheries system at the PSDA Community Group (Pokmas PSDA), with solar-powered pumps and lights, shows a cost efficiency of Rp. 61,600,000 – Rp. 19,665,000 = Rp. 41,935,000 (assuming the equipment's life cycle cost is 10 years), resulting in a cost savings of 67%.   Keywords: Fisheries, PSDA Community Group, Solar Energy, TTG